2022
DOI: 10.3390/cancers14122949
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Components of Protein Homeostasis Pathway Can Be Targeted to Produce Drug Synergies with VCP Inhibitors in Ovarian Cancer

Abstract: Protein quality control mechanisms play an important role in cancer progression by providing adaptive responses and morphologic stability against genome-wide copy number alterations, aneuploidy, and conformation-altering somatic mutations. This dependency on protein quality control mechanisms creates a vulnerability that may be exploited for therapeutic benefits by targeting components of the protein quality control mechanism. Recently, valosin-containing protein (VCP), also known at p97 AAA-ATPase, has emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…HRI has been proven to increase fetal hemoglobin production via diminishing the expression of BCL11A, and this may be a potential therapeutic target for sickle cell disease [42]. Moreover, mifepristone activates cytotoxic effects through the eIF2AK1-mediated signal transduction pathway, promoting the drug synergies in ovarian cancer therapy [43]. In our study, we treated UECC with different concentrations of heme and found that heme increased the cell viability and invasiveness of UECC while, as expected, silencing NCOA1 could partially or even completely eliminate this effect of heme.…”
Section: Discussionmentioning
confidence: 99%
“…HRI has been proven to increase fetal hemoglobin production via diminishing the expression of BCL11A, and this may be a potential therapeutic target for sickle cell disease [42]. Moreover, mifepristone activates cytotoxic effects through the eIF2AK1-mediated signal transduction pathway, promoting the drug synergies in ovarian cancer therapy [43]. In our study, we treated UECC with different concentrations of heme and found that heme increased the cell viability and invasiveness of UECC while, as expected, silencing NCOA1 could partially or even completely eliminate this effect of heme.…”
Section: Discussionmentioning
confidence: 99%